Lesotho : Statistical Annex. (IMF Staff Country Reports; Country Report ;, 2001)
The statistical data on gross domestic product, consumer price indices, central government operations, government revenue and grants, Southern African Customs Union (SACU) operations, government expenditure, and outstanding government domestic debt in Lesotho have been presented. The paper presents data on monetary survey, sectoral distribution of commercial bank credit to the private sector and statutory bodies, interest rates paid by the central bank on commercial bank deposits, comparative money market rates, balance of payments, services and income account, Lesotho miners in South Africa, and related economic indices.